Investigating the Relationship between Key Factors and Customer Satisfaction in an Online Shopping Platform - Gan Kia Hui; Sheue Hui Lim; Praveen Aronkar; Wei Sheng Lim; Xinyuan Lin; Maisarah Binti Meor Hashim; Mas Dalyna Binti Saadon; Desta Safa Nur Akmalia; Rosa Ayu Dewanti; Rr. Shafana Syafiyyah Putri; Vedika Bajpayee; Daisy Mui Hung Kee (AIBPM Publisher, 2024)
The COVID-19 pandemic during the 2020's has led to the rapid growth of e-commerce in recent years, which has necessitated a greater understanding of the factors that contribute to customer satisfaction in the online context. This study was conducted to investigate the relationship between key factors and customer satisfaction in Lazada. The online survey was carried out to collect data and information from 100 respondents. In this study, five independent variables (efficiency, reliability, assurance, responsibility, and security) are investigated. The results indicate assurance and responsibility have a significant and positive influence on customer satisfaction whereas efficiency has a significant and negative impact on customer satisfaction. This study aligns with several Sustainable Development Goals (SDG), such as decent work and economic growth (SDG 8), as well as responsible consumption and production (SDG 12). In conclusion, this study contributes to the existing literature on e-commerce by providing empirical evidence on the impact of e-marketing strategies on customer satisfaction.